2004
DOI: 10.1063/1.1842360
|View full text |Cite
|
Sign up to set email alerts
|

In situ formation of two amorphous phases by liquid phase separation in Y–Ti–Al–Co alloy

Abstract: Abnormal behavior of supercooled liquid region in bulk-forming metallic glasses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
77
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(87 citation statements)
references
References 14 publications
5
77
1
Order By: Relevance
“…In order to design such metallic glasses, two perquisites should be considered: (1) Two different liquid phases should exist in the melt by proper addition of alloying element which has positive enthalpy of mixing with at least one of the constituent elements; and (2) Glass forming ability of the two liquid phases should be enough to ensure the formation of two different amorphous phases in the solid state. So far, the phase separation phenomena have been reported in several glass forming systems (Park et al, 2004;Mattern et al, 2005;Park et al, 2007, Chang et al, 2010. It has been also shown that droplet or interconnected type microstructure can be formed with two different microstructure formation mechanisms, i.e., spinodal decomposition or nucleation and growth which are determined by the alloy composition (Chang et al, 2010;Park et al, 2004;Park et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to design such metallic glasses, two perquisites should be considered: (1) Two different liquid phases should exist in the melt by proper addition of alloying element which has positive enthalpy of mixing with at least one of the constituent elements; and (2) Glass forming ability of the two liquid phases should be enough to ensure the formation of two different amorphous phases in the solid state. So far, the phase separation phenomena have been reported in several glass forming systems (Park et al, 2004;Mattern et al, 2005;Park et al, 2007, Chang et al, 2010. It has been also shown that droplet or interconnected type microstructure can be formed with two different microstructure formation mechanisms, i.e., spinodal decomposition or nucleation and growth which are determined by the alloy composition (Chang et al, 2010;Park et al, 2004;Park et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the phase separation phenomena have been reported in several glass forming systems (Park et al, 2004;Mattern et al, 2005;Park et al, 2007, Chang et al, 2010. It has been also shown that droplet or interconnected type microstructure can be formed with two different microstructure formation mechanisms, i.e., spinodal decomposition or nucleation and growth which are determined by the alloy composition (Chang et al, 2010;Park et al, 2004;Park et al, 2006). Design of such phase separating metallic glass may open a new field for structural or functional application of the metallic glass.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to use a liquid phase separation phenomenon existing in alloys * corresponding author; e-mail: tkoziel@agh.edu.pl containing at least one pair of elements that exhibit a positive heat of mixing. By proper alloying, it is possible to increase the glass forming abilities of both melts, and a two-phase metallic glass can be formed upon cooling [10][11][12]. If a GFA of one melt will be not sufficient, amorphous-crystalline composites, containing sphericalshape crystalline precipitates embedded in an amorphous matrix, can be obtained [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The phase separation of the liquid is determined by the thermodynamic properties of the alloy system. For the phase separated metallic glasses reported in [6][7][8][9][10][11][12] the critical temperature of liquid-liquid phase separation T c is above the liquidus temperature. In this case, phase separation leads to a special microstructure with a length scale up to several microns and some self-similar features are observed by transmission electron microscopy [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In bulk metallic glass forming alloys the addition of elements with strong positive enthalpy leads to improvement of ductility [4] or glass forming ability [5] in a certain composition range. Phase separated metallic glasses have been prepared in several alloy systems by rapid quenching the melt : Zr-Y-Al-Ni [6], Zr-La-Al-Ni-Cu [7], Zr-Y-Co-Al [8], Ni-Nb-Y [9], Zr-Nd-Al-Co [10] , Cu-(Zr,Hf)-(Gd,Y)-Al [11], and Zr-(Ce,Pr,Nd)-Al-Ni [12]. The phase separation of the liquid is determined by the thermodynamic properties of the alloy system.…”
Section: Introductionmentioning
confidence: 99%